Pendidikan Humanis: Perbandingan Paradigma Pendidikan Humanis Al-Ghazali dan Ki Hadjar Dewantara: Humanistic Education: A Comparative Study of Al-Ghazali's and Ki Hadjar Dewantara's Paradigms - Ahmad Royani (Fenomena, 2012)
Education is the only effort to build human beings as whole persons. The development of a country depends on the development of education for its society. Schools, as formal educational institutions, systematically plan various educational environments that provide numerous opportunities for students to engage in diverse learning activities. A good educational concept to implement is Ki Hadjar Dewantara's humanistic concept, which focuses on human freedom in expressing their potential and abilities, and Imam Al-Ghazali's religious humanistic education concept to attain the pleasure of Allah SWT. Pendidikan merupakan upaya untuk membangun manusia sebagai pribadi yang utuh. Perkembangan suatu negara bergantung pada perkembangan pendidikan bagi masyarakatnya. Sekolah sebagai lembaga pendidikan formal secara sistematis merencanakan berbagai lingkungan pendidikan yang menyediakan banyak kesempatan bagi peserta didik untuk melakukan berbagai kegiatan pembelajaran. Konsep pendidikan yang baik untuk diterapkan adalah konsep humanis Ki Hadjar Dewantara, yang berfokus pada kebebasan manusia dalam mengekspresikan potensi dan kemampuan mereka, serta konsep pendidikan humanis religius Imam Al-Ghazali untuk mendapatkan ridho dari Allah SWT.